THE STUDY OF SOAKING TIME IN LIUID SMOKE OF CATFISH (Pangasius hypopthalmus) WITH ADDING CHITOSAN AS ANTIMICROBE DURING ROOM TEMPERATURE STORAGE - Pasaribu, Anto Saut; Buchari, Dewita; ', Suparmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was intended to determine the different of soaking time using chitosan as antimicrobe on catfish during room temperature storage. The method used in this study was experimental with soaking the catfish on to smoked liquid and chitosan liquid during 45 minutes (X1), 75 minutes (X2) with 0, 7, 14, and 21 days of storage times.The parameters analysis were total plate count; organoleptic analysis is (consistence, flavor, aroma and texture); and chemical analysis.The results showed that the applied treatment had giving real different on the quality of smoked catfish during room temperature storage. The treatment of 75 minutes (X2) soaking time are was best treatment based on the total plate count, whereas the treatment of 45 minutes (X1) soaking time are the best treatment based on the organoleptic analysis and chemical analysis.Keywords: Catfish , liquid smoked, chitosan